The Relationship between Clean Water Facilities, Building Conditions, and Toilet Ownership with Events Stunting among Months Toddlers in The Working Area of The Taktakan Public Health Center - Prihayati; Lanjar Wasis Sembada; Rita Ramayulis (Health and Technology Journal (HTechJ), 2024)
Stunting is a growth and development disorder experienced by children due to poor nutrition, recurrent infections, and inadequate psychosocial stimulation. Research purposes This is analyzing and knowing the relationship between clean water facilities and conditions building and ownership of toilets with the occurrence of stunting in toddlers aged 6-59 years month in the working area of the Taktakan Community Health Center, Serang City in 2023. Design This research is an analytical observational study with a research plan Cross section. The sample in this study was 62 toddlers aged 6-59 months. Primary data collection uses questionnaires with direct interviews, Secondary data was obtained from data on toddlers at the Taktakan Community Health Center, Serang City 2023. The results of the univariable analysis show that most of the toddlers are in the category very short at 24.2%, most of the clean water facilities are in the good categoryamounted to 67.7%, and latrine ownership in the good category amounted to 91.9%. Results of bivariable analysis stated that there was a significant relationship between the means clean water (p=0.000), building condition (p=0.000), and latrine ownership (p=0.010) with the incidence of stunting in the Taktakan Community Health Center working area, Serang City in 2023. Suggestions are given to improve supervision as well give more attention to pregnant women and babies about the importance of adequate nutrition and living environment.